Analisis Pembuktian dalam Perkara Tindak Pidana Siber - Zulfiah Zulfiah; Nabillah Karimah; Harvila Intan Nurmala Sari; Sintong Arion Hutapea (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Rapid developments in digital technology have increased the complexity of cybercrime and posed new challenges in its detection. Unlike traditional crimes, evidence in cyber cases relies on electronic evidence that has special characteristics, such as digital formats that are susceptible to change, storage on remote servers, and connections to aspects of digital forensics. The aim of this research is to analyze the evidentiary mechanism in cybercrime cases based on the Criminal Procedure Law (KUHAP), the Electronic Transaction Information Law (UU ITE) and other related laws and regulations. The research methodology used is normative law with case studies of legislative approaches and court decisions regarding the validity of electronic evidence. The study found that although electronic evidence is recognized as valid evidence in Indonesia's criminal justice system, obstacles to its implementation remain, including inconsistent legal interpretations, a lack of operational standards for digital forensic investigations, and limited human resources in law enforcement agencies. Therefore, to ensure the validity of evidence in cyber crimes, it is necessary to harmonize laws and regulations, increase the capacity of law enforcement officials, and strengthen cooperation between institutions.